2007
DOI: 10.1177/104063870701900213
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Neoplasia in Llamas and Alpacas (Oregon State University, 2001–2006)

Abstract: Prevalence and type of neoplastic disease were determined in 551 camelid submissions (368 alpacas [Lama pacos], 180 llamas [Lama glama], and 3 cases in which species was not identified) over a 5-year period. Forty neoplasms were identified in 38 animals (6.9%). Prevalence of neoplasia in llamas was higher (11%) than in alpacas (4.9%). Mean age of camelids with neoplasia was 9.42 +/- 4.9 years. Mean age of alpacas with neoplasia (5.48 +/- 3.7 years) was significantly less than of llamas with neoplasia (12.53 +/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
74
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(83 citation statements)
references
References 22 publications
1
74
0
5
Order By: Relevance
“…12 Although mixed mammary tumors are common in dogs 6 and have been reported in humans, 8 these tumors have been rarely reported in other domestic animals. To the authors' knowledge, this is the first report describing the histologic and immunohistochemical features of a carcinoma in a mixed mammary tumor in a 13-year-old llama.…”
mentioning
confidence: 99%
“…12 Although mixed mammary tumors are common in dogs 6 and have been reported in humans, 8 these tumors have been rarely reported in other domestic animals. To the authors' knowledge, this is the first report describing the histologic and immunohistochemical features of a carcinoma in a mixed mammary tumor in a 13-year-old llama.…”
mentioning
confidence: 99%
“…11 It has been shown that lymphoma occurs at a younger age in alpacas when compared with llamas. 1,11,22 One case of subcutaneous lymphoma affected a young animal (1.5-year-old alpaca), whereas the other 2 cases of cutaneous lymphoma affected adult animals (9-year-old alpaca and 20-year-old llama). In other species, the clinical course of epitheliotropic CTCL can range from months to a few years 6 ; however, the small number of cases that have been reported in SACs restricts any ability to draw reliable conclusions with regards to the clinical course of this disease in camelids.…”
mentioning
confidence: 99%
“…A retrospective study describing the prevalence and types of neoplasia diagnosed in SACs for the Pacific Northwest observed that cutaneous and mucocutaneous neoplasms were the most common types of tumors diagnosed in the llama and alpaca; however, none of those cases were cutaneous lymphoma. 22 A 2010 review of skin disease in the alpaca reported a single case of subcutaneous lymphoma in a young alpaca. 19 Additionally, a larger study describing the immunophenotypic characterizations of 26 camelid malignant round cell tumors identified a single case of epitheliotropic cutaneous T-cell lymphoma (CTCL) in an aged llama.…”
mentioning
confidence: 99%
“…4,7,8,13 In the horse, melanomas most frequently occur in gray horses, and it is believed that a disturbance in melanin metabolism occurs during the graying process, leading to overproduction and accumulation of melanoblasts in the dermis. 4,13 Retrospective studies 2,9,12 reported the prevalence of neoplasia in the New World camelid to be 1.0-8.3%. To date, there has been 1 report of nonmetastatic intraocular melanoma in a 2-year-old female alpaca, 3 The malignant melanoma in the case here originated in the skin at the mucocutaneous junction of the left nares and was locally invasive, with metastasis to the regional lymph nodes and lung.…”
mentioning
confidence: 99%